Performance, morphology and photophysics of high open-circuit voltage, low band gap all-polymer solar cells. Issue 1 (21st November 2014) - Deshmukh, Kedar D.; Qin, Tianshi; Gallaher, Joseph K.; Liu, Amelia C. Y.; Gann, Eliot; O'Donnell, Kane; Thomsen, Lars; Hodgkiss, Justin M.; Watkins, Scott E.; McNeill, Christopher R.
Abstract : Promising efficiencies and a high open-circuit voltage are demonstrated for a novel low band-gap all-polymer photovoltaic blend. Abstract : The microstructure and photophysics of low-band gap, all-polymer photovoltaic blends are presented. Blends are based on the donor polymer BFS4 (a dithienyl-benzo[1, 2- b :4, 5- b ]dithiophene/5-fluoro-2, 1, 3-benzothiadiazole co-polymer) paired with the naphthalene diimide-based acceptor polymer P(NDI2OD-T2). Efficiencies of over 4% are demonstrated, with an open circuit voltage of greater than 0.9 V achieved. Transmission electron microscopy reveals a relatively coarse phase-separated morphology, with elongated domains up to 200 nm in width. Near-edge X-ray absorption fine-structure (NEXAFS) spectroscopy and atomic force microscopy (AFM) measurements reveal that the top surface of BFS4:P(NDI2OD-T2) blends is covered with a pure BFS4 capping layer. Depth profiling measurements confirm this vertical phase separation with a surface-directed spinodal decomposition wave observed. Grazing-incidence wide-angle X-ray scattering (GIWAXS) measurements confirm that BFS4 and P(NDI2OD-T2) are semicrystalline with both polymers retaining their semicrystalline nature when blended. Photoluminescence spectroscopy reveals incomplete photoluminescence quenching with as much as 30% of excitons failing to reach a donor/acceptor interface. Transient absorption spectroscopy measurements also find evidence for rapid geminate recombination.